Labor Absorption and Its Impact on Gross Regional Domestic Product - Made Ika Prastyadewi; Agus Suman; Devanto Shasta Pratomo (Muhammadiyah University Press, 2013)
The objective of this study is to examine the determinants of labor absorption in the trade, hotel and restaurant sector and its impact on Gross Regional Domestic Product/GRDP at Bali Province. This study is important due to the fact that the GRDP in this sector is the highest compared to other sector but the labor absorption is lower than the agriculture sector. This study used panel data comprising 9 regencies/cities at Bali Province in the period 2003-2009 including fixed effect model and simultaneous equation model of Two-Stage Least Square. The results showed that GRDP, working age population, and the minimum wage have positive effect on employment, while the educated unemployment has no significant effect on the employment in the trade, hotel and restaurant sector. In addition, increases in employment and workers productivity have positive and significant effects the GRDP in the trade, hotel and restaurant sector at Bali Province.